Design, synthesis, biological evaluation, kinetic studies and molecular modeling of imidazo-isoxazole derivatives targeting both α-amylase and α-glucosidase inhibitors - Etab AlRashidi; Siwar Ghannay; Abuzar E.A.E. Albadri; Majdi Abid; Adel Kadri; Kaiss Aouadi (Heliyon)
Herein, a novel set of imidazo-isoxazole derivatives containing thiourea and urea scaffolds were synthesized, characterized (1H NMR, 13C NMR, and elemental analysis). These compounds were biologically evaluated for their α-amylase and α-glucosidase inhibitory activity, identifying 5f as the most active (IC50 26.67 ± 1.25 μM and 39.12 ± 1.83 μM against α-amylase α-glucosidase, respectively), better than the standard, acarbose. Enzymatic kinetic results showed that 5f and acarbose complete competitive type inhibitors. The structure-activity relationship (SAR) demonstrated that undergoing substitutions on R1 and R2 groups attached to the thiourea/urea moiety chains controlled the activity. Besides, in-silico ADMET study showed that almost title compounds exhibited satisfactory pharmacokinetic properties. In molecular docking study, the top performing compound (5f) exhibited higher binding energies (−5.501 and −6.414 kcal/mol, respectively) showing crucial interactions and that snuggly fit in their active site. To shed light on their mechanism of action, molecular dynamic (MD) simulations approach executed at 100 ns duration authenticated the high stability of 5f-1B2Y and 5f-3A4A complexes. The results of this investigation disclosed that compound 5f may serve as a potential lead, accomplished with in vivo studies, for the management of diabetes.